Evidence Brief: Strengthening Care for People with Chronic Diseases in Ontario - Wilson, MG; Lavis, JN; Moat, KA; Guta, A (My University, 2016)
An assessment of what is known about problems related to care for people with chronic diseases, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of strengthening care for people with chronic diseases.
Keywords: care; chronic; diseases; people; Ontario